From the East to the South, and Back? International Solidarity Movements in Belgium and New Histories of the Cold War, 1950s–1970s. (2nd September 2015) - Christiaens, Kim
Abstract : To date, accounts of international solidarity movements with an orientation towards the Third World have remained strongly embedded in 1968 historiography and largely unconnected to Cold War history. This article aims to position these solidarity movements within the broader history of the Cold War and to explore their relevance to efforts at globalizing and entangling the history of North-South and East-West relations. Building on arguments developed by Cold War historians, and examples drawn from Belgium, it identifies three themes which have been largely unexamined in mainstream accounts of international solidarity movements, yet serve as toeholds for challenging traditional premises of 1968 historiography. First, it argues that East-West networks and communist movements constituted a space for North-South encounters and campaigns. Second, it assesses the role of Third World agency, which reveals a little known side of international solidarity campaigns that brings us to sectors and ideas beyond the radical new left and to diplomacy, human rights, and North-South networks. Third, this article analyzes how solidarity with the Third World was a source of détente and East-West cooperation. What is revealed from this analysis is a Europeanization of the Third World that became a projection screen for ideas of Europe's past and future and united East-West and North-South campaigns.